2008
DOI: 10.1007/s11095-008-9780-3
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylamino Acid Esters as Biodegradable and Reversible Transdermal Permeation Enhancers: Effects of Linking Chain Length, Chirality and Polyfluorination

Abstract: DDAK, highly effective, broad-spectrum, biodegradable and reversible transdermal permeation enhancer, is promising candidate for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 36 publications
4
33
0
Order By: Relevance
“…6. Baseline measurements of skin resistance varied from 11.0 to 15.8 kΩ/cm 2 , which is consistent with previous reports (14). Compared to treatment with water (control), ME-lo and ME-hi promoted a 2.5 and 4.2-fold (p< 0.05) decrease in skin electrical resistance, respectively, suggesting that microemulsion treatment decreased the barrier function of the skin.…”
Section: Evaluation Of Electrical Resistance Of Skinsupporting
confidence: 90%
See 1 more Smart Citation
“…6. Baseline measurements of skin resistance varied from 11.0 to 15.8 kΩ/cm 2 , which is consistent with previous reports (14). Compared to treatment with water (control), ME-lo and ME-hi promoted a 2.5 and 4.2-fold (p< 0.05) decrease in skin electrical resistance, respectively, suggesting that microemulsion treatment decreased the barrier function of the skin.…”
Section: Evaluation Of Electrical Resistance Of Skinsupporting
confidence: 90%
“…Skin samples were mounted in diffusion cells, and the donor and receptor compartments were filled with phosphate buffered saline (PBS); after 20 min of equilibration, the electrodes were inserted in the donor and receptor compartments for measurement of baseline skin resistance (14,15). Immediately thereafter, PBS in the donor compartment was replaced with 100 mg of water (control), ME-lo or ME-hi for 8 h. This time point was chosen since most of the differences between ME-lo and ME-hi skin penetration enhancement were observed after 8 h. By the end of the experiment, skin samples were washed with water and blotted dry.…”
Section: Evaluation Of Electrical Resistance Of Skinmentioning
confidence: 99%
“…Some authors found different permeation rates for enantiomers, while other studies showed no enantiomeric differences in the permeation [20−22,34−36]. Similarly, investigations of interactions of individual CPE enantiomers with the skin provided opposite results [20,22,37,38]; therefore additional studies are needed to be performed to answer whether the skin is an enantioselective membrane and given its mechanism of action, enhancer conformation can influence its enhancing properties or the differences in the permeation rates between the individual enantiomers are not related to any stereoselective interactions, but they can be explained only by different physicochemical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Acyclic nucleoside phosphonates cPr-PMEDAP, PMEG, and PMEDAP (20) and the permeation enhancer DDAK (19) were synthesized as described previously. All other chemicals were from Sigma-Aldrich (Schnelldorf, Germany).…”
Section: Chemicalsmentioning
confidence: 99%
“…This enhancer was found to possess highly favorable properties: broadspectrum activity, negligible toxicity, and biodegradability by esterases. Moreover, its effect on the skin barrier was reversible (19).…”
Section: Introductionmentioning
confidence: 99%